2022
DOI: 10.1128/spectrum.02503-21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Plasmid-Mediated Types 1 and 3 Fimbriae Associated with Biofilm Formation in Multidrug Resistant Escherichia coli from Diseased Food Animals in Guangdong, China

Abstract: Biofilms allow bacteria to tolerate disinfectants and antimicrobials, as well as mammalian host defenses, and are therefore difficult to treat clinically. Most research concerning biofilm-related infections is typically focused on chromosomal biofilm-associated factors, including types 1 and 3 fimbriae of biofilm-forming Enterobacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition, more than 50% of the strains co-carried bla CTX–M , such a high prevalence of bla CTX–M showed that most of these strains belonged to MDR strains. Meanwhile, the co-carriage of 16s RNA methylase, PMQRs, and fosfomycin genes suggested that the mcr -positive strains were also reservoirs of numerous resistance genes ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more than 50% of the strains co-carried bla CTX–M , such a high prevalence of bla CTX–M showed that most of these strains belonged to MDR strains. Meanwhile, the co-carriage of 16s RNA methylase, PMQRs, and fosfomycin genes suggested that the mcr -positive strains were also reservoirs of numerous resistance genes ( Guo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can easily acquire multi-drug resistance, owing to its ability to accumulate multiple resistance genes, primarily through horizontal gene transfer of mobile elements. Currently, its acquisition of genes encoding extended-spectrum β-lactamases (ESBLs), carbapenem-hydrolyzing ß-lactamase (CHßls), 16S rRNA methylases, plasmid-mediated quinolone resistance (PMQR), and plasmid-mediated glutathione S-transferase (PMGST) is of great clinical concern ( Simoni et al, 2021 ; Yin et al, 2021 ; Guo et al, 2022 ), accelerating the evolution of drug resistance, making colistin the last-resort antibiotic for treating infections caused by multi-drug resistant bacteria. The use of colistin in livestock as a growth promoter has been banned in China ( Wang et al, 2020 ) due to increasing polymyxin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bacterial biofilms on the surfaces of indwelling medical and dental devices make the treatment of infections increasingly difficult ( Linklater et al, 2021 ). Biofilms formation within the host have been implicated in diseases such as cystic fibrosis, urinary tract infections, and endocarditis ( Guo et al, 2022 ). The negative impacts of microbial biofilms are incalculable, resulting in an annual loss of millions of US dollars ( Cattò and Cappitelli, 2019 ).…”
Section: Introductionmentioning
confidence: 99%